Cytoskeleton-functionalized synthetic cells with life-like mechanical features and regulated membrane dynamicity - Novosedlik, Sebastian; Reichel, Felix; van Veldhuisen, Thijs; Li, Yudong; Wu, Hanglong; Janssen, Henk; Guck, Jochen; van Hest, Jan (Nature Chemistry, 2025)
The cytoskeleton is a crucial determinant of mammalian cell structure and function, providing mechanical resilience, supporting the cell membrane and orchestrating essential processes such as cell division and motility. Because of its fundamental role in living cells, developing a reconstituted or artificial cytoskeleton is of major interest. Here we present an approach to construct an artificial cytoskeleton that imparts mechanical support and regulates membrane dynamics. Our system involves amylose-based coacervates stabilized by a terpolymer membrane, with a cytoskeleton formed from polydiacetylene fibrils. The fibrils bundle due to interactions with the positively charged amylose derivative, forming micrometre-sized structures mimicking a cytoskeleton. Given the intricate interplay between cellular structure and function, the design and integration of this artificial cytoskeleton represent a crucial advancement, paving the way for the development of artificial cell platforms exhibiting enhanced life-like behaviour. (Figure presented.)
CRIS-Team Scopus Importer:2025-01-31